Niobium-buffered tantalum for a superconducting fluxonium qubit - Zi shuo Li; Ting ting Guo; Wen qu Xu; Li li Shi; Kai xuan Zhang; Quan Zuo; Tian shi Zhou; Guo zhu Sun; Pei heng Wu (Materials Research Express, 2025)
We use a magnetron sputtering system to grow a tantalum film on a sapphire substrate with a niobium buffer layer at room temperature. The tantalum film is in α -phase, which is preferred for superconducting quantum devices. We fabricate a superconducting heavy fluxonium qubit with this niobium-buffered tantalum film, which demonstrates good performance. Forbidden transitions and sideband transition phenomena between specific energy levels are observed. Due to the specific design parameters, the fluxonium described herein exhibits high anharmonicity while maintaining a long decoherence time in the higher energy states, making it well-suited for use as a qudit and enabling high-dimensional quantum computation. With further optimization of the film deposition process, superconducting qubits other than fluxoniums with higher performance are expected to be obtained using these multilayer films grown at room temperature.